OPTIMIZATION APPROACH FOR DESIGN OF SPUR GEAR BASED ON GENETIC ALGORITHM - PANNEERDHASS R; ANANDHAKUMAR S (Innovare Journal of Engineering and Technology, 2019)
Abstract -Â  The problem of designing spur gear with minimum mass and smaller size without violating the constraints plays a major role in today's industrial world, since the most commonly encountered mechanical power transmission require low weight. This paper presents an genetic approach to reduce the weight and thickness of the gear, also increases the power transmitting capacity and effectiveness using genetic algorithm (GA). It can be observed that the proposed optimal design with GA has the potential to yield considerably better solutions than the traditional heuristics. At the same time, the GA offer a better understanding of the trade-offs between various constraints. Â  Key words: Optimal design, genetic algorithm, Spur gear